2020
DOI: 10.3390/plants9050630
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Growth-to-Ripening Time Interval Induced by Abscisic Acid and Synthetic Auxin affecting Transcriptome and Flavor Compounds in Cabernet Sauvignon Grape Berry

Abstract: Abscisic acid (ABA) and auxin are important hormones controlling the ripening progression of grape berry, and both the initiation and duration of ripening can dramatically affect the berry quality. However, the responses of flavor compounds to the hormones are inadequately understood. In this study, ABA and synthetic auxin α-naphthaleneacetic acid (NAA) were sprayed on Cabernet Sauvignon berries before véraison, and comparative transcriptomic and metabolic analysis were conducted to investigate the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“…Gamma-butyrolactone and β-farnesene were lower in NAA wines in the current study and in Cabernet Sauvignon NAA wines from a different trial (Böttcher et al 2022), but β-farnesene was higher in wine made from NAA-treated Riesling fruit (Böttcher et al 2012). The norisoprenoid β-damascenone was higher in NAA wines in the current study (Table 1) and in Riesling NAA wines (Böttcher et al 2012) and was also shown to be higher in the juice of NAA-treated Cabernet Sauvignon berries, along with higher free and total norisoprenoids (He et al 2020). The increase observed was correlated with NAA-induced transcriptional changes to genes involved in carotenoid metabolism, such as CCD4a and 4b (He et al 2020(He et al , 2021.…”
Section: General Wine Composition and Wine Volatile Analysissupporting
confidence: 51%
See 2 more Smart Citations
“…Gamma-butyrolactone and β-farnesene were lower in NAA wines in the current study and in Cabernet Sauvignon NAA wines from a different trial (Böttcher et al 2022), but β-farnesene was higher in wine made from NAA-treated Riesling fruit (Böttcher et al 2012). The norisoprenoid β-damascenone was higher in NAA wines in the current study (Table 1) and in Riesling NAA wines (Böttcher et al 2012) and was also shown to be higher in the juice of NAA-treated Cabernet Sauvignon berries, along with higher free and total norisoprenoids (He et al 2020). The increase observed was correlated with NAA-induced transcriptional changes to genes involved in carotenoid metabolism, such as CCD4a and 4b (He et al 2020(He et al , 2021.…”
Section: General Wine Composition and Wine Volatile Analysissupporting
confidence: 51%
“…The causes of the maintenance of berry mass in the later stages of ripening of NAA‐treated fruit could be manifold. Considerable changes to the expression of many genes involved in a wide range of processes occur in auxin‐treated grapes (Ziliotto et al 2012, Dal Santo et al 2020, He et al 2020, 2021). Changes to the waxy cuticle that would reduce berry transpiration is one possible mechanism by which NAA treatment might prevent berry mass loss, as cuticular conductance along with vapour pressure deficit are key determinants of transpiration mass loss (Rogiers and Holzapfel 2015, Zhang and Keller 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, since vitispirane A, vitispirane B, and MHO exhibited lower levels in ABA-treated berries in consecutive two seasons ( Table S2 ), ABA treatments or the increased endogenous ABA may negatively regulate the accumulation of these compounds by down-regulating VviCCD4a ( Figure 2 B). The pre-veraison NAA treatment was found to increase total norisoprenoids at E-L 35 and E-L 36 stages in grape berries [ 21 ] and β-damascenone level in wine [ 3 ]. Different from ABA treatment, NAA effect on norisoprenoid biosynthesis, by comparison to ABA biosynthesis, appeared to be more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…One report mentioned that the exogenous application of auxin-like compounds can delay ripening and simultaneously affect the concentration of norisoprenoids in wines [ 3 ]. Moreover, our previous study preliminarily investigated the effects of ABA and synthetic auxin 1-naphthaleneacetic acid (NAA) on anthocyanins and volatile compounds in grape berry at the beginning of ripening [ 21 ]. In the present study, we further evaluated the roles of ABA and NAA in regulating the biosynthesis of norisoprenoid at both the metabolite and transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%